Proceedings of SPE Annual Technical Conference and Exhibition 2007
DOI: 10.2523/109016-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Viscoelasticity on Displacement Efficiency--From Micro- to Macroscale

Abstract: The displacement efficiency (De) in porous media is usually analyzed by the ratio of the macro pressure gradient driving force and interfacial tension (IFT) between the driving fluid and residual oil. However, when the pressure gradient is constant, macro forces cannot explain the increase in De by driving fluids with elastic properties. Therefore, the change of micro forces acting on residual oil between driving fluids with and without elastic properties is analyzed.This paper shows the influence of viscoelas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…It was found that if an elastic fluid flows over dead ends, normal stresses between oil and polymer solution are generated in addition to the shear stresses resulting from the long molecular chains [36,37]. Therefore, polymer molecules impose a larger force on oil droplets and thus pull them out of dead ends.…”
Section: Pulling Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that if an elastic fluid flows over dead ends, normal stresses between oil and polymer solution are generated in addition to the shear stresses resulting from the long molecular chains [36,37]. Therefore, polymer molecules impose a larger force on oil droplets and thus pull them out of dead ends.…”
Section: Pulling Effectmentioning
confidence: 99%
“…For oil-wet porous media, residual oil is attached on the rock surface in the form of a continuous oil film (Figure 3(2)). Wang et al [8,36] compared the velocity profile of a Newtonian and a non-Newtonian fluid in a capillary and observed that the velocity gradient near the capillary wall for the elastic fluid is noticeably higher than that for the Newtonian fluid (Figure 7). Therefore, a stronger force is produced during flow of polymer solutions compared to water, which thus facilitates stripping the oil films off rock surface and eventually promotes the microscopic displacement efficiency [39][40][41][42].…”
Section: Stripping Effectmentioning
confidence: 99%
“…While traversing through the constricted pore throat region of the reservoir, the injected slug would generate extensional, viscoelastic stress that led to the difference in their behavior. Several types of research were carried out to investigate the role of viscoelasticity in additional recovery during chemical flooding . It was concluded that viscoelasticity is an additional recovery mechanism that could mobilize some of the residual oil.…”
Section: Introductionmentioning
confidence: 99%
“…In oil recovery, the viscoelasticity of the pushing fluid has been considered through its extensional viscosity [6] which can induce significant increase of flow resistance in a porous medium. Recently it has been suggested that 1 the development ofsignificant normal stress differences could be at the origin ofenhanced oil recovery [7][8][9][10][11][12]. This normal stress effect has nevertheless not been demonstrated yet, and the physics at work not understood either:…”
Section: Introductionmentioning
confidence: 99%